2021
DOI: 10.3390/inorganics9060049
|View full text |Cite
|
Sign up to set email alerts
|

Binding Properties of a Dinuclear Zinc(II) Salen-Type Molecular Tweezer with a Flexible Spacer in the Formation of Lewis Acid-Base Adducts with Diamines

Abstract: In this paper we report the binding properties, by combined 1H NMR, optical absorption, and fluorescence studies, of a molecular tweezer composed of two Zn(salen)-type Schiff-base units connected by a flexible spacer, towards a series of ditopic diamines having a strong Lewis basicity, with different chain length and rigidity. Except for the 1,2-diaminoethane, in all other cases the formation of stable 1:1 Lewis acid-base adducts with large binding constants is demonstrated. For α,ω-aliphatic diamines, binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…[24][25][26][27][28][29] Among Zn(salen)-type complexes, colourful derivatives from the 2,3-diaminomaleonitrile, Zn(salmal), are certainly those more interesting for their optical absorption and fluorescence emission properties upon deaggregation. [30][31][32][33][34][35][36][37] In order to further explore these varied characteristics, we have chosen a Zn(salmal) complex, 1, having different substituents on the salicylidene rings. In particular, we found that the presence of 5-tert-butyl-bulky substituents makes this complex sufficiently soluble in a range of coordinating/non-coordinating solvents, giving us the possibility to explore its spectroscopic properties in solution, even in comparison to previous studies on amphiphilic Zn(salmal) complexes with longer alkyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29] Among Zn(salen)-type complexes, colourful derivatives from the 2,3-diaminomaleonitrile, Zn(salmal), are certainly those more interesting for their optical absorption and fluorescence emission properties upon deaggregation. [30][31][32][33][34][35][36][37] In order to further explore these varied characteristics, we have chosen a Zn(salmal) complex, 1, having different substituents on the salicylidene rings. In particular, we found that the presence of 5-tert-butyl-bulky substituents makes this complex sufficiently soluble in a range of coordinating/non-coordinating solvents, giving us the possibility to explore its spectroscopic properties in solution, even in comparison to previous studies on amphiphilic Zn(salmal) complexes with longer alkyl substituents.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46] In particular, derivatives from the 2,3-diaminomaleonitrile, Zn(salmal), are characterized by relevant optical spectroscopic changes in relation of the nature of the aggregate species or monomeric adducts. [47][48][49][50][51][52][53] We have demonstrated that in solution of weak coordinating solvents a 5-tert-butyl substituted Zn(salmal) complex (1) forms relatively stable adducts which easily transmetalate with divalent ions of the first transition series, but with a different rate. 54 In particular, the transmetalation with Cu 2+ ions is faster than that with other cations, regardless of the nature of the counteranion.…”
Section: Introductionmentioning
confidence: 99%
“…Zn(salen)-type complexes are characterized by varied photophysical properties strongly related to the structure of the diimine bridge [21,22], substituents on the salicylidene rings, and non-coordinating or coordinating nature of the solvent [23][24][25]. Among them, colorful complexes derived from 2,3-diaminomaleonitrile, Zn(salmal), are the most interesting also for their fluorescent properties [26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%